Serial CRP (C-reactive protein) Monitoring in COVID-19 Pneumonia for the Assessment of Severity, Ventilatory Support Requirement and Predicting Early Lung Fibrosis (Journal of Medicine, 2022)
Introduction: Robust data of CRP is available in bacterial infection, and now it can be utilized in Covid- 19 pneumonia pandemic initial assessment of severity and planning of treatment.Materials and Methods: Multicentric, prospective, observational and interventional study conducted during July 2020 to May 2021 included 1000 Covid-19 cases confirmed with RT PCR. All cases were assessed with lung involvement documented and categorized on HRCT thorax, oxygen saturation, inflammatory marker as CRP at entry point and follow up. Age, gender, Comorbidity and use BIPAP/NIV and outcome as with or without lung fibrosis as per CT severity were key observations. Statistical analysis is done by using Chi square test.Observations and analysis: Age (50 years) and gender (male versus female) has significant association with CRP in predicting severity [p